Coexpression of Human Hepatic Uridine Diphosphate Glucuronosyltransferase Proteins: Implications for Ontogenetic Mechanisms and Isoform Coregulation. (26th December 2019) - Liu, Yuejian; Badée, Justine; Takahashi, Ryan H.; Schmidt, Stephan; Parrott, Neil; Fowler, Stephen; Mackenzie, Peter I.; Coughtrie, Michael W. H.; Collier, Abby C.
Abstract: Uridine diphosphate glucuronosyltransferases (UGTs) catalyze glucuronidation to facilitate systemic and local clearance of numerous chemicals and drugs. To investigate whether UGT expression is coregulated in human liver, we analyzed the protein expression of UGTs 1A1, 1A3, 1A4, 1A6, 1A9, 2B7, 3A1, and 3A2 using western blots from 164 healthy human liver samples, comparing expression with age and sex. UGT1A6 levels were significantly higher in children than adults, and UGT3A1 and 3A2 expression significantly increased with age from childhood to age >65 yearas. In children aged <18 years, UGT1A4/1A9 protein expression was significantly correlated, but not for adults aged >18 years. UGT1A3 expression was always significantly correlated with other UGT1A isoforms in all adults aged >18 years. In individuals aged ≥12 years, expression of UGT1A1/1A4, UGT1A1/1A6, UGT1A1/1A9, and UGT1A4/1A6 significantly correlated, which was not observed in children aged <12 years. In contrast, UGT1A4/2B7 showed significant correlation in children aged <12 years, but not in individuals aged ≥12 years, and this was observed in female but not male individuals. Expression of UGT1A6/1A9 and UGT3A1/3A2 correlated in the entire sample population, but UGT3As did not correlate with other UGTs. These correlations were sex dependent, as UGT1A3/1A1, UGT1A4/2B7 and UGT3A1/3A2 correlated more highly in male than female individuals, while UGT1A4/1A6 protein correlated more significantly in female than male individuals. This is the first report on the ontogeny of UGT3A isoforms, showing maximal expression in the elderly, and is the first demonstration that UGT isoforms commonly coexpress in vivo, in both age‐dependent and sex‐dependent manners.